Acute renal failure in renal allograft recipients and patients with native kidneys - Carvalho, Maria Fernanda Cordeiro [UNESP]; Barretti, Pasqual [UNESP]; Inuzuka, Luciana Midori [UNESP]; Sueto, Milena [UNESP]; Nishimura, Marcia Regina [UNESP]; Caramori, Jaqueline Costa Teixeira [UNESP]; Balbi, André Luis [UNESP]; Corrêa, Luiz Antonio [UNESP]; Soares, Vitor Augusto [UNESP] (Taylor & Francis, 1997)
In order to evaluate the role of underlying disease in the high mortality observed in acute renal failure (ARF) and risk factors related to the development of oliguric ARF in renal allograft recipients, two groups were selected: 34 patients with native kidneys, aged 16 and 57 years, and presenting ischemic ARF caused by cardiovascular collapse, with no signs of infection at the time of diagnosis; and 34 renal allograft recipients who developed ARF immediately after transplantation, without rejection. ARF was defined either as 30% increase of basal plasmatic creatinine in patients with native kidneys or non-normalization of plasmatic creatinine at day 5 after transplantation in renal allograft recipients; oliguria as diuresis ≤ 400 mL/24 h. There were no differences in age, male frequency, oliguria presence and duration, need for dialysis, and infection episodes for renal allograft recipients and patients with native kidneys. The development of sepsis (3% and 41%) and death rate (3% and 44%) were higher in patients with native kidneys (p < 0.01). The renal allograft recipients with both oliguric (n = 18) and nonoliguric (n = 16) ARF were evaluated and no difference was observed in the recipient's age, donor's age, cold ischemia time, time elapsed until plasmatic creatinine normalization, donor's plasmatic creatinine or urea, and mean arterial pressure. No differences were observed between the groups regarding frequency of infection episodes during ARF and frequency of death. In conclusion, renal allograft recipients presented a lower death rate and were less susceptible to sepsis. Cold ischemia time, age, and hemodynamic characteristics of the donor did not affect the development of oliguria.
Keywords: creatinine; acute kidney failure; adolescent; adult; conference paper; controlled study; dialysis; female; human; kidney allograft; kidney ischemia; kidney transplantation; major clinical study; male; mortality; oliguria; priority journal; recipient; sepsis; Adolescent; Adult; Age Distribution; Brazil; Evaluation Studies; Female; Graft Rejection; Humans; Incidence; Kidney Failure, Acute; Kidney Transplantation; Male; Middle Aged; Risk Factors; Sex Distribution; Survival Rate